2020
DOI: 10.2174/1567202617666200117103931
|View full text |Cite
|
Sign up to set email alerts
|

MiR-340 Reduces the Accumulation of Amyloid-β Through Targeting BACE1 (β-site Amyloid Precursor Protein Cleaving Enzyme 1) in Alzheimer’s Disease

Abstract: Background: Alzheimer’s disease (AD) is the most common neurodegenerative disease, and the accumulation of amyloid-β is the initial process in AD. MicroRNAs (miRNAs) are widely known as key regulators of the accumulation of amyloid-β in AD. This study analyzed the potential effects and possible internal mechanisms of miR-340 on AD. Methods: The expression of miR-340 in senescence-accelerated mouse prone-8 (SAMP8) mouse and senescence-accelerated mice/resistant-1 (SAMR1) mouse was evaluated by qRT-PCR (quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…We searched the literature (Kou et al, 2020; Patel et al, 2019; Sadlon et al, 2019) with the database (http://www.targetscan.org/vert_71/, Agarwal et al, 2015; http://starbase.sysu.edu.cn/index.php, J. H. Li et al, 2014) online analysis, the miRNAs associated with AD were intersected with miRNAs that targeted the POT1 3′‐UTR region in the database (Figure 4a), and the results showed that the intersection of the data in three databases was miR‐340‐5p. A previous study showed that miR‐340‐5p was downregulated in the hippocampus of AD model mice and reduced amyloid‐β accumulation by targeting BACE1 (Tan et al, 2020). The expression of miR‐340‐5p in AD mice and Aβ 42 ‐induced HT22 cells was detected by qRT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We searched the literature (Kou et al, 2020; Patel et al, 2019; Sadlon et al, 2019) with the database (http://www.targetscan.org/vert_71/, Agarwal et al, 2015; http://starbase.sysu.edu.cn/index.php, J. H. Li et al, 2014) online analysis, the miRNAs associated with AD were intersected with miRNAs that targeted the POT1 3′‐UTR region in the database (Figure 4a), and the results showed that the intersection of the data in three databases was miR‐340‐5p. A previous study showed that miR‐340‐5p was downregulated in the hippocampus of AD model mice and reduced amyloid‐β accumulation by targeting BACE1 (Tan et al, 2020). The expression of miR‐340‐5p in AD mice and Aβ 42 ‐induced HT22 cells was detected by qRT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Increasingly, studies reported that miRNAs might be involved in the pathogenesis of AD (Kou et al, 2020; T. Li et al, 2020). miR‐340‐5p was downregulated in the hippocampus of AD model mice and reduced amyloid‐β accumulation by targeting BACE1 (Tan et al, 2020). In our study, bioinformatics analysis and dual‐luciferase reporter assay were performed to identify miRNAs that can target the telomere protection protein POT1 and finally found the targeted binding relationship between miR‐340‐5p and POT1.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-200a-3p also reduces the expression of BACE1 and is confirmed to be decreased in the hippocampus of APP/PS1 and SAMP8 mice as well as in blood plasma from AD patients (113). MicroRNA-340 is decreased in the hippocampus of an AD mouse model and associated with the overproduction of Aβ by targeting BACE1 (114). MicroRNA-31 reduces the mRNA levels of BACE1 and improves memory deficits in AD triple-transgenic (3xTg-AD) female mice (115).…”
Section: Non-coding Rnas In Admentioning
confidence: 88%
“…However, results solid for millions of mature patients affected by AD have failed to emerge. At the moment perspectives exist only for early stages of the disease [ 108 110 , 121 , 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of a third, miR-340, has been shown to reduce the activity of presenilin 1, the most important enzyme for the generation of Aβ. The excess of miR-340 in brain cells reduces therefore the AD development [ 110 ].…”
Section: Neurodegeneration and Its Diseasesmentioning
confidence: 99%